EXAMINING OLDER ADULTS DIGITAL INCLUSION THROUGH THE LENS OF INTERSECTIONALITY AND CONTINUITY THEORY - van Leeuwen, Cora; Jacobs, An; Mariën, Ilse; Consortium, Digital Ageing (AoIR Selected Papers of Internet Research, 2023)
The possible ubiquitous presence of technology connected to the internet and a growing ageing population has necessitated a renewed interest in the digital inclusion of older adults. The focus on chronological age is a form of ageism as it erases the heterogeneity of the community while over-emphasising a physical attribute. We argue that by introducing a conceptual framework incorporating the intersectionality theory (Crenshaw, 1990) and the continuity theory (CT) (Atchley, 1989, 1999) it is possible to explain the differences found in digital in/exclusion that go beyond chronological age. This would enable a more individualised approach to the current curriculum of digital skill acquirement and to help affect lasting change in digital technology adoption by older adults. A thematic analysis (Braun&Clarke, 2006) on 26 semi-structured interviews, with self-proclaimed digital technology users aged between 66 and 84, was used to test this conceptual framework. By using both theories it was possible to explain why chronological age cannot be used as an indicator of use or non-use. Rather examining the intersections of their identity in combination with their investments in habits and skills can explain why some older adults benefit more and are able to make use of the internet in comparison to others.